Barriers to adopting evidence-based practice: A cross-sectional study among undergraduate nursing students in Vietnam - Pham Thi Thu Hien; Luu Thi Thuy; Nguyen Thi Yen Hoai (Tehran University of Medical Sciences, 2023)
Background & Aim: As the future nursing workforce, evidence-based practice is one of the key competencies for undergraduate nursing students in delivering safe and quality care. While plenty of studies investigate nurses' evidence-based practice, understanding this topic is limited among nursing students. Thus, this study aimed to identify barriers and associated factors to adopting evidence-based practice among undergraduate nursing students in Vietnam. Methods & Materials: A cross-sectional descriptive study was conducted on 395 undergraduate nursing students who were conveniently selected at a public university in Central Vietnam from March to May 2022. A questionnaire was administered to collect information about general characteristics and barriers to implementing evidence-based practice regarding knowledge, practice, authority, setting, and research utilization. Data were analyzed using SPSS 20.0 with descriptive statistics, independent t-test, one-way analysis of variance, and Pearson's correlation coefficients. Results: Among 395 participants, most of them faced barriers regarding knowledge (91.9%), practice (96.2%), authority (89.1%), clinical setting (92.2%), and research utilization (96.2%). The most mentioned barriers were related to research utilization and clinical settings. Barriers to adopting evidence-based practice were significantly associated with a level of seeking information about research/scientific evidence and a level of participating in research/implementing evidence-based practice (p<.05). Moreover, knowledge barriers were related to age, school year, and sources of data for searching (p<.05). Conclusion: Undergraduate nursing students have faced many barriers when adopting scientific evidence into clinical practice. Supporting students in addressing these barriers is necessary to enhance their evidence-based practice competency.